2015
DOI: 10.1177/0141076815599674
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing junior doctors’ choices of future specialty: trends over time and demographics based on results from UK national surveys

Abstract: Objective: To study trends in factors influencing junior doctors' choice of future specialty. Design: Respondents were asked whether each of 15 factors had a great deal of influence on their career choice, a little influence or no influence on it. Percentages are reported of those who specified that a factor had a great deal of influence on their career choice. . Prospects for promotion were less important to recent cohorts (16%) than older cohorts (21%), as were financial prospects (respectively, 10% and 14%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 16 publications
7
59
2
4
Order By: Relevance
“…In our study PCPs perceived a higher influence for their career decision of their families than non-PCPs. This confirms similar results in other settings [2124]. Meanwhile, PCPs reported less influence of chiefs and professors in their career decision.…”
Section: Discussionsupporting
confidence: 91%
“…In our study PCPs perceived a higher influence for their career decision of their families than non-PCPs. This confirms similar results in other settings [2124]. Meanwhile, PCPs reported less influence of chiefs and professors in their career decision.…”
Section: Discussionsupporting
confidence: 91%
“…These findings agree with previous work highlighting the importance of previous experience in shaping career choice,1 but a number of complex and evolving factors2 such as the role of domestic circumstances have an increasing effect as careers develop and circumstances change 3…”
supporting
confidence: 91%
“…For example, much research has shown that female doctors and medical students place higher value on work‐life balance and lifestyle factors than their male counterparts 12‐18 . However, more recent studies have suggested that, overall, a greater proportion of the medical workforce now appear to value life‐oriented factors such as work‐life balance over job‐related factors such as income 8,9‐24 . This may relate to the fact that in many countries more women than men are entering medicine 25‐27 .…”
Section: Introductionmentioning
confidence: 99%
“…This may relate to the fact that in many countries more women than men are entering medicine 25‐27 . However, this does not fully explain the changing patterns; research has indicated that the desire for work‐life balance is of increasing importance to male medical students, trainees or residents and fully‐qualified doctors 4,21,23,28,29 …”
Section: Introductionmentioning
confidence: 99%